Instant Unfermented Coconut Sap Beverage as a Nutritive Beverage with Potential Health Benefits - H. P. D. T. Hewa Pathirana; C. N. Hitigedera; W. M. K. Lakdushighe; L. L. W. C. Yalegama; J. A. D. Madusanka (International Coconut Community, 2025)
Coconut (Cocos nucifera) sap is a nutritious liquid which oozes from the phloem vessels of coconut inflorescence. Dried coconut sap powder was developed as an instant beverage from unfermented coconut sap collected from a novel sap collection device and its quality was assessed. The sap was mixed with maltodextrin (DE-10) (Treatment 1; 3%, Treatment 2; 4%, Treatment 3; 5% and Treatment 4; 6%) and the solution was fed to a spray dryer. The powder of sap was packed in a triple-laminated aluminium pouch and stored at 4±2 oC for quality analysis. The data was analyzed through Minitab 16 software. The recovery percentage of powder was 17.05±2.45% and it showed good quality character for moisture (0.80±0.20%), bulk density (0.05±0.00 g/L), tapped density (0.068±0.00 g/L), hygroscopicity (19.05±0.34%), and solubility (96.72±0.87 %). The browning index (13.53±0.00) and lightness (86.75±2.17) of the sample were assessed. Scanning electron microscopic (SEM) view showed an even distribution of particles. The dilution ratio (D1:8 %, D2: 10 %, D3: 12 %) of powder was analyzed through sensory evaluation. Appearance and odour of the beverage were not affected significantly (p>0.05) with the dilution ratio. The analysis showed that it contained protein (1.44 ±0.11%), ash (0.99±0.01%), mineral (Na: 15.4±0.13mg/Kg, K: 369.4±0.87 mg/Kg, Ca: 46.8±0.89 mg/Kg, Mg: 7.7±0.52 mg/Kg), crude fiber (0.08±0.01%), total sugar (90.67±2.66%), moltodextrin (24.40±2.55%), sucrose (31.47±2.77%), glucose (16.04±0.23%), fructose (18.76±1.25%) and total phenol (138.69±0.17 mg GAE/ 100 g). One cup (100 ml) of sap contains higher nutrients with natural minerals to achieve high consumer demand.